Analisis Hukum Fikih Muamalah Kontemporer terhadap Penggunaan Aset Kripto dalam Zakat Produktif - Patih, Husnama (Journal of Industrial and Syariah Economics, 2024)
Contemporary muamalah jurisprudence continues to evolve in line with the dynamics of the global economy. The emergence of crypto assets as a digital financial instrument presents new challenges in the application of Islamic law, especially in terms of productive zakat. This study analyzes the law of using crypto assets as an object of productive zakat. Through the maqashid Sharia approach and a review of contemporary fiqh literature, this study concludes that the potential use of crypto assets as an object of productive zakat needs to be studied more deeply. Although crypto assets have different characteristics from fiat currencies, the general principles of productive zakat are still relevant to be applied. Several things must be observed: the volatile nature of crypto, regulations that are not yet consistent in various countries, and the potential risks associated with using crypto assets. This research hopes that it can participate in developing Islamic law that is adaptive to the times and provide guidance for Muslims in managing crypto assets in a Sharia manner.